Students’ Perceptions on Reciprocal Peer Tutorial Assessment in an Undergraduate Course in Process Metallurgy - Matinde, Elias (Education sciences, 2019)
Tutorials play a key role in the teaching and learning of engineering sciences. However, the efficacy of tutorials as platforms for providing personal and academic support is continuously being challenged by factors such as declining faculty-to-student ratios and students’ under-preparedness. This study adopted reciprocal peer tutorial assessment as an instructional strategy in a capstone course in Process Metallurgy. The findings from highlighted the delicate balance between the obvious benefits and the unintended consequences of adopting reciprocal peer assessments during tutorials. The obvious benefits of RPTA included opportunities for synergistic peer learning, healthy competition among students, self-directed learning, among others. However, the benefits of RPTA were negated by factors such as low level of trust among peers, anxiety over year marks, time constraints, and discomfort due to perceived incompetency when compared to their peers. Finally, the findings from the present study provided opportunities for iterative design and continuous improvement.